Pengaruh Likuiditas, Leverage, Profitabilitas, Dan Ukuran Perusahaan Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Consumer Cyclicals Yang Terdaftar Di BEI Periode 2021 – 2024 - Adi Nurcahyo, Daffiansyah; Sunarto, Sunarto (Jurnal GeoEkonomi, 2025)
The following research aims to analyze and test the influence of liquidity, leverage, profitability and company size on stock returns in manufacturing companies belonging to one sector, namely consumer cyclicals, during the 2021-2024 period listed on the (BEI). The amount of data used was 241, which was obtained through the purposive sampling method. In the analysis process, this research applies various techniques, including descriptive statistical tests, normality tests, classic assumption tests consisting of multicollinearity, heteroscedasticity and autocorrelation tests, multiple linear regression tests. Apart from that, model testing was also carried out using the F test and R² test, and hypothesis testing using the t test. The results of the research show that liquidity and profitability have no effect on stock returns, while company size has a positive effect on stock return.